Quality of life and its associated factors among primary caregivers of children with cerebral palsy living in Sarlahi and Rautahat districts of Nepal. - Pandit,Bina (2018)
ABSTRACT: Background: Cerebral Palsy (CP) is one of the major causes of childhood disability. It appears to be similar in developed and developing countries and theoretically it was estimated that every year around 1116-1675 children are having CP in Nepal (Thapa, 2016). Children with CP need more attention and care from primary caregiver. This can affect Quality of Life (QOL) of primary caregiver. Objective: The main objective of this study is to determine the QOL and factors associated with QOL among primary caregivers of children with cerebral palsy. Methodology: This study was comparative cross-sectional study. Comparison was done between primary caregivers of children with CP in rehab and non rehab group. Sample was collected through Purposive sampling technique. Face to face interview was done by using well structured questionnaire. Data were analyzed through SPSS 16 version. Results: Median age of caregivers was 34 years and there was significant difference between age in two groups (p=0.028). 83 (86.5%) caregivers were female with significant difference between gender in rehab and non rehab group (p=0.03). Majority of primary caregivers were mother 71 (74%) in both groups. Among all 96 caregivers, 78.1% of caregivers had poor QOL. There was no significant difference between QOL in rehab and non-rehab group (p=0.42). Factors associated with QOL in rehab groups was illiteracy (OR=7.33, p=0.005), aggressive nature of child (OR=11, p=0.050), uncooperative nature of child (OR=9, p=0.025), poor knowledge about child condition (OR=15.55, p< 0.001), and low financial support (OR=5.2, p=0.051). Similarly, factor associated with QOL in non-rehab group was GMFCS level of child (p< 0.001) and more perceived stress (OR=5.53, p=0.048). Conclusion: Based on overall result of QOL, majority of primary caregivers was mother and had poor QOL and there was no significant difference between overall QOL of caregivers in Rehab and Non-rehab group. Major factors associated with poor QOL of primary caregivers of children with CP are education level of caregivers, GMFCS level of child, nature of child, knowledge about child condition, financial support and perceived stress. QOL of caregivers must be focused by rehab professionals to achieve adequate functional outcome in children with CP. Key words: Quality of life, Primary caregivers, Cerebral Palsy.